Research plan: Utilizing multiple regression analysis to evaluate factors influencing customer satisfaction with banking services - Othman, Khalid Talib (Edelweiss Applied Science and Technology, 2025)
The main objective of the research will be to evaluate factors that affect customer satisfaction with the banking service provided through multiple regression analysis. As the banking industry has geared itself towards the driver of customer satisfaction as the paradigm for its success, the precise determinants for the same need to be unearthed. The examination of this paper includes service quality, responsiveness, personal interaction, security, and their direct contributions to levels of customer satisfaction. A structured survey is being designed to collect quantitative data on a representative sample of bank customers regarding various aspects that will be analyzed through multiple regression to identify and quantify the influence of each factor. The research is carried out using a quantitative technique, and the main analysis approach in this respect is a statistical analysis technique. Each of the variables will be looked at separately in an attempt to find out not only which one has a greater effect but how the change or fluctuation in the variables would relate to customer perceptions and, hence, overall satisfaction. The findings are anticipated to illuminate pragmatic insights for banking institutions in providing directions regarding which areas the services should be worked on to bring about a significant enhancement in customer satisfaction. The research will thus have set up the provision for the banking institutions to improve their services based on data and enhance the strength of customer relationships. The research also highlights possible constraints, such as demographic variance in customer expectations, to present a complex understanding of satisfaction determinants within a banking context. Therefore, as a result, the research intends to enhance theoretical knowledge and, at the same time, provide practical solutions toward customer satisfaction to enable banks to build better operational service models that are centered on the needs of the customers.